Criopreservação de oócitos de Prochilodus lineatus (Valenciennes, 1836) (Teleostei, Prochilodontidae) - Ribeiro, Douglas de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The decades cryobiology seeks to conserve the maternal genome in fish through gamete preservation, but the techniques currently available run into problems such as low permeability of the membranes, the large the amount of yolk and the sensitivity of gametes to cold. Work on the subject has been carried out, however unsystematically and majority form with cold temperate species. Due to lack of information on the subject with Neotropical fish, the aim of this work is to develop a protocol for the freezing of Prochilodus lineatus oocytes for this, was evaluated using different salt solutions (Ringer and Ringer's lactate solution, Hank's balanced salt solutions (HBSS) with and without calcium, and the solution for salmonid eggs) as a means of maintaining and extending the viability of oocytes. We also assessed the toxicity of three cryoprotectants agents (ACPs) the Dimethyl sulfoxide (DMSO), Propylene glycol (PG), and Methanol (MET), to (1) the development of vitrification protocols with exposure, 2.5, 5.0 and 7.5 min. in molarities the 6 M 8 M 10 M CPA; and (2) for the construction of slow cooling protocols with CPAs with increasing incorporation of the baths evaluated toxic effects on fertility in 0.5 M, 1 M, 2 M and 4 M. It was evaluated the lower the sensitivity of oocytes temperature (2.5 ° C) storage on four 30, 60, 90 and 120 minutes. Oocytes underwent slow cooling in nitrogen steam evaluating the morphological injuries due to exposure to the CPAs and freezing. The results showed that only with HBSS without calcium and were able to maintain the state of gametes not activated, however, they do not provide the extent of viability of oocytes, allowing that they continue to suffer from degradation by storage time, similarly to the oocytes retained only in ovarian fluid. The high sensitivity of oocytes to the CPAs and the cold was found. The toxicity of the higher molarities of CPAs (6 M, 8 M and 10 M) at all exposure times, precludes ...

A décadas a criobiologia busca a conservação do genoma materno em peixes por meio da conservação de gametas, porém as técnicas disponíveis atualmente esbarram em problemas como a baixa permeabilidade das membranas, o grande volume de vitelo e a sensibilidade dos gametas ao frio. Trabalhos acerca do assunto vem sendo realizados, contudo de forma não sistemática e de forma majoritária com espécies de clima temperado a frio. Devido a carência de informações sobre o tema com peixes neotropicais, objetivou-se neste trabalho desenvolver um protocolo para o congelamento de oócitos de Prochilodus lineatus, para isso, foi avaliado o uso de diferentes soluções salinas (solução de Ringer e Ringer lactato, solução salina balanceada de Hank (HBSS) com e sem cálcio, e solução para ovos de salmonídeos) como meio de manutenção e extensão da viabilidade dos oócitos. Também foi avaliado a toxicidade de três agentes crioprotetores (ACPs) o Dimetilsulfóxido (DMSO), Propilenoglicol (PG), e Metanol (MET), visando (1) a elaboração de protocolos de vitrificação, com exposição de 2,5, 5 e 7,5 min. em molaridades de 6 M, 8 M e 10 M de ACP; e (2) para a construção de protocolos de congelamento lento com incorporação dos ACPs em banhos crescentes avaliado os efeitos tóxicos sobre a fertilização em 0,5 M, 1 M, 2 M e 4 M. Avaliou-se a sensibilidade dos oócitos a baixa temperatura (2,5°C) em quatro tempos de estocagem 30, 60, 90 e 120 minutos. Oócitos foram submetidos ao congelamento lento em vapor de nitrogênio avaliando as injúrias morfológicas geradas pela exposição aos ACPs e ao congelamento. Os resultados obtidos mostraram que somente a HBSS com e sem cálcio foram capazes de manter o estado não ativado dos gametas, porém, as mesmas não proporcionaram a extensão da viabilidade dos oócitos, permitindo a que estes continuassem a sofrer a degradação pelo tempo de estocagem, de forma similar aos oócitos mantidos...
Keywords: Biotecnologia animal; Peixe - Pesquisa; Criobiologia; Baixas temperaturas - Pesquisa; Peixe - Histologia; Animal biotechnology